Análise experimental do comportamento a incêndios naturais de vigas de aço protegidas com tintas intumescentes - Marcus César Quintão Araújo (2024)
The use of intumescent paints for passive fire protection in fire-safety projects has increased in recent years. Positive aspects like superior quality surface finishing and effective thermal barrier performance have led numerous researchers to conduct studies aiming to characterize this type of protection, describing the behavior of intumescent coatings. In Brazil, the design of passive protection systems is prescribed by ABNT NBR 14323:2013. However, these definitions do not apply to intumescent coatings as they present non-linear physicochemical properties triggered by the burning of gas and the formation of a non-homogeneous foamy compound during the heating process. Therefore, the application of these protective materials in civil construction depends mainly on experimental studies developed by manufacturers based on foreign regulatory prescriptions. This study aims to determine the physical and kinetic parameters describing the behavior of passive protection provided by intumescent paint on steel beams exposed to natural fires. For this purpose, tests were carried out on short steel profiles with different section factors and different dry protection thicknesses in an electric oven to determine the temperature profile of the protected element and the effective thermal conductivity of the intumescent paint, as prescribed by EN-13381:2010. Full-scale tests were also carried out on protected beams under natural fire conditions. Through these tests, the temperature gradients acting on the protected metallic substrate, the temperature of gases resulting from the combustion, and the deformations caused by applied loading were determined. Additionally, the development of the intumescent layer, the influence of localized heating, and potential critical points formed in the intumescent layer post-fire were evaluated. The results obtained from these beam tests were applied to European regulatory equations to derive the thermal conductivity as a function of the average temperature of the fire gases and protected steel. The formation of the carbonaceous layer showed cracks in the edges, indicating the need for caution during application to ensure structural safety. Despite this, it was observed that the intumescent paint showed excellent behavior in fire protection for profiles with a high section factor, avoiding the degradation of mechanical properties due to fire and consequently the emergence of failures.